Subthreshold swing model using scale length for sub-10 nm junction-based double-gate MOSFETs - Hakkee Jung (International Journal of Electrical and Computer Engineering (IJECE), 2020)
We propose an analytical model for subthreshold swing using scale length for sub-10 nm double gate (DG) MOSFETs. When the order of the calculation for the series type potential distribution is increased it is possible to obtain accuracy, but there is a problem that the calculation becomes large. Using only the first order calculation of potential distribution, we derive the scale length λ1 and use it to obtain an analytical model of subthreshold swing. The findings show this subthreshold swing model is in concordance with a 2D simulation. The relationship between the channel length and silicon thickness, which can analyze the subthreshold swing using λ1, is derived by the relationship between the scale length and the geometric mean of the silicon and oxide thickness. If the silicon thickness and oxide film thickness satisfy the condition of (Lg-0.215)/6.38 > tsi(=tox), it is found that the result of this model agrees with the results using higher order calculations, within a 4% error range.